Pengembangan Keprofesian Berkelanjutan Guru melalui Penelitian Tindakan Kelas - Nizaruddin, Nizaruddin; Murtianto, Yanuar Heri; Nuvitalia, Duwi; Sutrisno, Sutrisno; Zuhri, Muhammad Saifuddin (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
Teacher professionalism always views doing something that is right and good (do the right thing and do it right). As a consequence, he will always look for strategic and systematic ways in his learning process, so as to create a conducive and enjoyable learning situation. This community service activity aims to provide training and assistance for teachers at SMK N 6 Semarang so that they have the knowledge and skills in making proposals, instruments, and reports of classroom action research (CAR). The method used to achieve this goal is by training more questions and answers and practice as well as assistance in making class action research proposals, instruments and reports. The training material is presented with more practice than theory, with a ratio of 25% theory to 75% practice. The expertise of the PKM team is very helpful and useful in solving community service partner problems so that teachers at SMK N 6 Semarang have knowledge and skills related to PTK. Community service activities have been able to increase teachers' understanding in making class action research proposals, making research instruments and using Mendeley for reference management. This is in line with the increase in the average pre-test score of 61.69 which increased to 75.81.